Penyelesain Vehicle Routing Problem (VRP) dalam Penugasan Kendaraan dan Penentuan Rute untuk Meminimasi Biaya Transportasi pada PT. XYZ dengan Menggunakan Algoritma Genetika - Ahmad Fauzan Abdurrahman; Ari Yanuar Ridwan; Budi Santosa (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
In the process of transportation it is very in accordance with the route, the route the mode / vehicle goes to the destination. Route about the number of vehicles and which locations are passed. PT XYZ is a company engaged in the fast moving consumer goods (FMCG), with fields that make the flow of goods going higher so that the distribution of goods becomes fast and frequent. The distribution process is carried out using 1 fleet in each customer. Currently in the process of distributing goods, companies still use utilities that are used, so that the availability of empty space in capacity still occurs and this makes transportation costs high. Combining (considering) some customers is possible, while considering the time window, capacity and some products. This study discusses the route by considering various constraints to get the route, the number of vehicles, increasing the utility of each vehicle and the optimal distance so as to minimize transportation costs. Using a genetic algorithm that is preceded by the nearest neighbour algorithm is used to resolve this complication. Later the route will be formed and get the number of vehicles, increase the number of vehicles and the optimal distance. These results make an increase in vehicle utility by an average of 35.317%, an increase in the number of vehicles by 34.05%, and a distance of 10.075% thus saving transportation costs by 26.56% from the initial conditions.